The best $m$-term trigonometric approximations of the classes of periodic functions of one and many variables in the space $B_{q,1}$ - K.V. Pozharska; A.S. Romanyuk (Researches in Mathematics)
Exact order estimates are obtained of the best $m$-term trigonometric approximations of the Nikol'skii-Besov classes $B^r_{p, θ}$ of periodic functions of one and many variables in the space $B_{q,1}$. In the univariate case ($d=1$), we get the orders of the respective approximation characteristics on the classes $B^r_{p, θ}$ as well as on the Sobolev classes $W^r_{p, {\boldsymbol{α}}}$ in the space $B_{∞,1}$ in the case $1\leqslant p \leqslant ∞$.